HUBUNGAN TINGKAT KERUSAKAN DENGAN BIAYA PERBAIKAN JALAN - Nafsul Hanif; Muhammad Isya; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2023)
Aside caused by an increase in the community's need for vehicle transportation facilities, road damage can also be caused by the condition of the soil base, unstable pavement and weathering of the soil surface. Immediate handling this situation is needed to prevent complexity due to road damage. The aimed of this study was to identify the relationship between the level of road damage and the cost of damage repair. This research was conducted on the 3.5 km at Keuniree-Simpang Sanggeu road which is divided into 7 segments. Primary data were selected by actual field surveys which are geometric data and the level of road damage. While the estimated repair costs were obtained from the area of road damage multiplied by the unit price of the work. A linear and non-linear regression analysis was used to analyze the relationship between independent (road demage) and dependen (cost of estimate demage repair) variables. The results showed that from the five models of linear and non-linear regression analysis (logarithmic, quadratic, cubic, and exponential), it was known that the level of road damage was significantly correlated to coat of damage repair (p=0.001). Based on the results of SEE and RMS can be known that the cubic regression model is the best mathematical equation in estimating repair costs (R=0,997) with the equation . This shows that the higher the road damage, the lower the repair costs and the lower the road damage, the higher cost is needed.